Indica rice anther culture: can the impasse be surpassed? - Silva, T.D. (My University, 2009)
During the past two decades numerous papers have been published on anther culture of rice. These studies clearly indicate that while anther culture is a technique that can be adopted for breeding japonica rice, it being a useful adjunct in indica rice breeding is still some way away. The main reasons why anther culture cannot be utilized for indica rice breeding is analyzed, and aspects that may be manipulated to achieve progress are presented in this review. The two stages of rice anther culture, callus induction and green plant regeneration, are genetically determined traits that show quantitative inheritance. Indica rice is known to have a recalcitrant genetic background that supports these traits poorly. While improvement of the genetic background through recombination or gene transfer remains possible, manipulation of culture media, particularly the nitrogen and carbon sources, has brought about substantial improvements in indica rice anther culture. Adjustments to pre- and post-culture conditions, that include application of various stresses on anthers before and after culture, also have had beneficial effects. The importance of reducing the tissue culture phase to achieve direct embryogenesis is discussed with special reference to improving green plant regeneration potential. The necessity to understand the processes involved in microspore embryogenesis is highlighted in order to support empirical knowledge and achieve a breakthrough in technology. In this regard, rice genome sequence information may be leveraged to elucidate functions of genes involved in microspore embryogenesis.